The Disruptive Innovation Potential and Business Case Investment Sensitivity of Open RAN - Kyoseva, Tsvetoslava; Poulkov, Vladimir; Lindgren, Peter (Journal of Mobile Multimedia, 2023)
Every telecom constantly faces the dilemma of when to invest in the next generation infrastructure network and how the investment would be monetized. The telco value proposition comprises products, services, processes, technologies, and network infrastructure. This paper explores making the business case out of Open RAN investment for a 5G network, where Open RAN is further researched if telcos perceive it as radical or disruptive innovation. As part of the research, different telecom companies are approached with a set of questions. The results are analysed and mapped in a Business Model Innovation chart. Furthermore, this paper also covers an analysis related to evaluating the sensitivity of how profitable a telco could be depending on Open RAN TCO investment for 5G deployments and the number of customers using value propositions – products, services and processes. Two sensitivity scenarios are simulated so various combinations could be observed before taking any further decision for Open RAN 5G business model implementation.